2019
DOI: 10.1039/c8fo01880d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enzymatic hydrolysis followed by transglutaminase-induced cross-linking on decreasing antigenicity and reserving partial interfacial properties of whey protein isolate

Abstract: Whey protein isolate (WPI) was hydrolyzed by alcalase and trypsin for three hydrolysis degrees (DHs), followed by transglutaminase (TGase) induced cross-linking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The free amino group contents of WPISA decreased significantly ( P < 0.05) after incubation with TGase for 4 h, which indicated that TGase-crosslinked WPISA formed, as was demonstrated by SDS-PAGE. TGase can catalyse the intra- and/or intermolecular cross-links among protein molecules by forming covalent isopeptide bonds between protein-bound glutaminyl and lysyl residues, and thus decrease the free amino group contents [29] . HUS significantly decreased ( P < 0.05) the free amino group contents of WPISA after cross-linking by TGase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free amino group contents of WPISA decreased significantly ( P < 0.05) after incubation with TGase for 4 h, which indicated that TGase-crosslinked WPISA formed, as was demonstrated by SDS-PAGE. TGase can catalyse the intra- and/or intermolecular cross-links among protein molecules by forming covalent isopeptide bonds between protein-bound glutaminyl and lysyl residues, and thus decrease the free amino group contents [29] . HUS significantly decreased ( P < 0.05) the free amino group contents of WPISA after cross-linking by TGase.…”
Section: Resultsmentioning
confidence: 99%
“…HUS treatment (e.g., 10, 20 and 40 min) significantly increased ( P < 0.05) the apparent viscosity of TGase cross-linked WPISA. This result may be attributed to the fact that the formation of high-molecular-weight polymers after cross-linking causes higher apparent viscosities [41] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] . However, there were no significant increases in the apparent viscosity of TGase cross-linked WPISA as the HUS time was increased from 10 to 40 min.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other studies demonstrated that Ara h 3 is sensitive to Alcalase hydrolysis and exhibits weak IgE binding capacity (Yu and Mikiashvili, 2020). Yu et al (2019) suggested that Alcalase was more effective in reducing the immunoreactivity of CM proteins than other enzymes, as it significantly lowered the IgE and IgG binding capacities of whey protein.…”
Section: Discussionmentioning
confidence: 83%
“…A moderate TGase treatment (treated for 60 min) could improve the emulsion properties of faba bean protein isolates by increasing the net surface charge ( 93 ). Yu et al ( 94 ) used TGase to cross-link Alcalase + trypsin hydrolyzed whey protein isolates, resulting in better emulsion properties, which is assumed to be due to increased flexibility and rearranged hydrophobic and hydrophilic amino acid residues. Solely hydrolyzed sodium caseinate by commercial enzymes could potentially self-assemble into network-like supramolecular particles, which drastically improved the stability of the emulsion by 400% ( 95 ).…”
Section: Emulsion Related Characteristics Of Proteinmentioning
confidence: 99%